Anthropogenic N deposition increases soil C storage by reducing the relative abundance of lignolytic fungi. Issue 2 (12th February 2018) - Entwistle, Elizabeth M.; Zak, Donald R.; Argiroff, William A.
Abstract: Atmospheric nitrogen (N) deposition has increased dramatically since preindustrial times and continues to increase across many regions of the Earth. In temperate forests, this agent of global change has increased soil carbon (C) storage, but the mechanisms underlying this response are not understood. One long‐standing hypothesis proposed to explain the accumulation of soil C proposes that higher inorganic N availability may suppress both the activity and abundance of fungi that decay lignin and other polyphenols in soil. In field studies, elevated rates of N deposition have reduced the activity of enzymes mediating lignin decay, but a decline in the abundance of lignolytic fungi has not been definitively documented to date. Here, we tested the hypothesis that elevated rates of anthropogenic N deposition reduce the abundance of lignolytic fungi. We conducted a field experiment in which we compared fungal communities colonizing low‐lignin, high‐lignin, and wood substrates in a northern hardwood forest that is part of a long‐term N deposition experiment. We reasoned that if lignolytic fungi decline under experimental N deposition, this effect should be most evident among fungi colonizing high‐lignin and wood substrates. Using molecular approaches, we provide evidence that anthropogenic N deposition reduces the relative abundance of lignolytic fungi on both wood and a high‐lignin substrate. Furthermore, experimental N deposition increased total fungal abundance on a low‐lignin substrate, reduced fungal abundance on wood, and had no significant effect on fungal abundance on a high‐lignin substrate. We simultaneously examined these responses in the surrounding soil and forest floor, in which we did not observe significant reductions in the relative abundance of lignolytic fungi or in the size of the fungal community; however, we did detect a change in community composition in the forest floor that appears to be driven by a shift away from lignolytic fungi and towards cellulolytic fungi. Our results provide direct evidence that reductions in the abundance of lignolytic fungi are part of the mechanism by which anthropogenic N deposition increases soil C storage.